Studi Carbon Footprint Dari Kegiatan Industri Pabrik Kelapa Sawit - Noviyani Puji; Aryo Sasmita; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Potential Indonesian palm oil showed that palm oil agribusiness role in the economy community, national and global. Environmental issues are closely linked to oil palm agribusiness one of them as a major contributor of greenhouse gas emissions (GHG). Riau Province is the largest palm oil producer in Indonesia, amounted to 7.3336 million tons with 146 units Palm Oil mill (POM). POM X is one which POM in the province of Riau. Total emissions resulting from palm oil mill X is 1,383,336.559 CO2 equivalent / year, with the largest emissions come from the use a boiler is 79%. Then followed with from diesel use is 18% and wastewater treatment is 3%. Mitigation measures to reduce GHG emissions in the POM X by capture methane gas into biogas. This method can reduce GHG emissions from the treatment of wastewater in the POM X is 89.261%. Keywords: Palm oil mill (POM), greenhouse gas (GHG) emissions